Applying multi-parity code to the quantum security protocol BB84 under different types of attacks - Abd al-Jabbar, Abd al-Ilah; Ahmad, Ibrahim Ahmad (al-Rafidain Engineering Journal : Regional Referred Scientific Journal., 2013)
ميكانيكية توزيع المفتاح الكمي تعتمد على مبادئ ميكانيكا الكم لتضمن تبادل امن للمفاتيح السرية بين المستخدمين. في هذا البحث تم محاكاة البروتوكول BB4 و تحسين أدائه عن طريق استخدام المماثلة المتعددة بدلا من المماثلة المتفردة في مرحلة تصحيح الأخطاء، كذلك فان أطوال المجاميع المحتسبة نكون متغيرة ديناميكا بطريقة انتقائية و بحسب معدل الخطأ في وحدة المعلومة الكمية QBER. تم في هذه الدراسة أيضا اخذ تأثير القناة الكمية على أداء البروتوكول BB4، عن طريق تطبيق أربعة أنواع مختلفة من القنوات (قناة مثالية، قناة ذات ضوضاء منخفضة. قناة ذات ضوضاء متوسطة و قناة عالية الضوضاء) بافتراض أن جميع القوات لا تحوي على خسائر. هذه الدراسة تضمنت كذلك اخذ تأثير ثلاثة أنواع من الهجمات على أداء البروتوكول BB4 (هجوم تقسيم عدد الفوتونات PNS، هجوم الاعتراض و إعادة الإرسال IR و هجوم مزيج من الهجومين السابقين PNS & IR). حيث أظهرت نتائج المحاكاة إن هجوم الاعتراض و إعادة الإرسال هو الأكثر تأثيرا على أداء البروتوكول BB4. Public-key encryption systems such as RSA [1] starts to be unable to withstand the attack of intruders due to the development of new cryptanalyst is methods and the huge increment of the processors computing power, it is obvious that if quantum computers are applied practically, then most of the current public-key cryptosystems would be vanished [2]. Conventionally one-time pad provides perfect information security but it has a big problem concerning the length of the random key which should be equal to the length of the plaintext. [3, 4, 5]. Quantum security is considered as an excellent and unbreakable way of encryption, it is based on the laws of quantum mechanics, which deals with elementary particles that do not have a precise location and speed simultaneously. This means that obtaining a particle’s location will destroy the information concerning its speed–and vice versa– (Heisenberg uncertainty principle) [6]. Bennett and Brassard [3] developed the protocol BB84 which is based on the uncertainty principle, it provides guaranteed security during the exchange of a secret key, it is worth to mention that according to this principle, it is impossible to know everything about the photons that carry the key bits. This means that intruders will certainly impose errors on the transmission channel that can be detected by the sender and receiver sides [6]. Many researchers have investigated this subject, for example : Stefan Rass and Christian Kollmitzer present an improvement to the error correction facility which yields a significant improvement on the BB84 protocol performance [7]. The classical cryptographic protocols, which are required for quantum key distribution are documented by Nikolaos Papanikolaou and Rajagopal Nagarajan then they suggest a model for the analysis of these protocols and verification of relevant security requirements. Alan Mink, Sheila Frankel and Ray Perlner [8] prepare an overview of the quantum key distribution (QKD) showing how QKD could be applied within security systems. In this paper, a new method for error correction is proposed using Multi-Parity instead of single parity and a comparison between three types of attacks on BB84 is included.